Explaining representation: a reply to Matthen. - Egan, Frances (Philosophical Studies, 2014)
The author offers a response to an article "How to Think about Mental Content" by Mohan Matthen, citing the failure of the researcher to understand the position of mentality though he often misconstrues passages that are clear in context. He argues on the particular construal of the role of representational content in computational models of cognition. He also cites that view of Matthen of computation is not sensitive to actual practice of representationalism.